Persepsi mahasiswa terhadap penggunaan program e-learning berbasis LMS pada Mata Kuliah Teknologi Budidaya Perikanan - Amirah Mustarin; Muhammad Wiharto (Seminar Nasional LP2M UNM, 2019)
The rapid development of information and communication technology has brought major changes in all fields, including the education sector. Educators are required to be able to choose and use various types of existing learning media. One alternative that is potentially used in learning is the e-learning learning method using the learning management system. This study aims to (a) find out the application of the LMS-based E-learning model to improve the quality of learning courses in Aquaculture Technology in the UNM Agricultural Technology Education Study Program. (b) To find out the LMS-based E-learning model for increasing interest in learning courses in Aquaculture Technology in the UNM Agricultural Technology Education Study Program. This research is an